HUBUNGAN ANTARA BERATNYA MANIFESTASI DERMATITIS ATOPIK DENGAN TINGGINYA SKALA KEPRIBAD IAN CEMAS PADA TES MMPI PADA PENDERITA DERMATITIS ATOPIK WANITA DI RSUD DR. SOETOMO - Iwan Sis Indrawanto (Universitas Muhammadiyah Malang, 2010)
Dermatitis Atopic, a kind of chronic skin disease that happens a lot in the world, tend to be increased in number and relatively difficult to treat. Most of them appear along with another atop ic condition such as Hay and asthma. The cause is not clearly un derstood yet. It’s thought to be the combination of genetics and environment. Many says that ther e’s emotional factor involved. It’s not the cause of the disease but it worsen or triggers the relaps. People of Dermatitis Atopic with anxious kind of personality have prone to relaps e easier than those who are not. This study figured out whether the degree of Dermatitits Atopic manifestation is correlated with the score o f anxious scale on MMPI of the Dermatitis Atopic female patien ts in Dr. Soetomo Public Hospital Surabaya. The method was analytical study with cr oss sectional approach, started from Juli 2009 until Desember 2009. The datas was taken from policlinics of Skin and Venereal Desease Department of Dr. Sutomo Pu blic Hospital Surabaya. Fivety three samples were taken, while 7 of them were failed due to high invalid MMPI score. The result showed that there was significant correlation between the degree of Dermatitits Atopic manifestation with the score of anxious scale on MMPI of the Dermatitis Atopic female pati ents. The correlation was medium to high. Keywords: Dermatitis Atopic, Anxious Personality, MMPI